The Portuguese Far Right: Between Late Authoritarianism and Democracy (1945-2015) - Marchi, R. (2019)
The book discusses the far right in the contemporary Portugal (1945-2015) within three different periods: the end of the authoritarian regime of António de Oliveira Salazar (1945-1974), the transition to democracy after the coup d’état of April 25th (1974-1982) and the democratic regime until the present (1982-2015). The analysis focuses on political groups and parties, social movements, ideologies, intellectuals and publications acting at the extreme right of the political spectrum of the Portuguese authoritarian regime and of the democratic regime, both on a national and international level. The book also contextualizes the Portuguese far right within the political thought and the organisational models of the wider European extreme right. A qualitative in-depth case study and the outcome of ten years of research, this book offers analysis of historical and contemporary primary sources, previously unexplored archives and in-depth interviews. Assessing the extent to which the behaviour of the far right is altered in different political environments and situations, this book makes an innovative and unique contribution to scholarship on the extreme right within southern Europe and will be of interest to students and scholars researching extreme right politics, as well as European history and politics more generally.